Cytotoxicity and Apoptosis of Cancer Cells by the Crude Extract From Chromolaena odorata (L.) King & Robinson - โทผล ดร.สุชาดา; วรานุสันติกูล ดร.ปิยาภรณ์; หาญภาคภูมิ ดร. ศรีสุดา; กังวานรังสรรค์ ดร. นิวัฒน์ (Journal of Food Health and Bioenvironmental Science, 2016)
Leaf, stem and root of Chromolaena odorata (L.) King & Robinson were extracted with aqueous, ethanol, methanol and hexane solvents. The crude leaf extracts with all solvents showed significantly higher percentage yield than those of stem and root. Cytotoxicity study of C. odorata extracts was performed on melanoma cell C32 using the MTT assay. The crude extracts which showed IC50 values less than 500 μg/ml (leaf with ethanol and hexane), were used with 500 μg/ml concentration at 24 and 48 hours for determination of melanoma cell C32 apoptosis induction using DAPI staining technique and DNA fragmentation using gel electrophoresis technique. The results showed morphological hallmarks in the early stage of apoptosis including chromatin condensation, chromatin fragmentation, nuclear fragmentation and apoptotic bodies. The specific biochemical changes in the late stage of apoptosis showed DNA fragmentation.